Economics of local people: Iskandar, Malaysia - Rabe, Noor Suzilawati; Mohammed Osman, Mariana; Bachok, Syahriah (Elsevier, 2014)
This paper discusses the implication of underlying regional economic theories and policies on social and economic development in Iskandar Malaysia. Furthermore, the study investigates local people’s knowledge and perception towards Iskandar Malaysia development as one of the main economic accelerators in the southern part of the Peninsular Malaysia. A questionnaire survey was conducted among the local people within the 5 flagship zones in Iskandar Malaysia regional economic development. The research had produced a picture on local people perception and knowledge towards the development in Iskandar Malaysia. Several social and economic issues and the impacts of these issues also identified in the research.